Scaffolding the attention-deficit/hyperactivity disorder brain using transcranial direct current and random noise stimulation: A randomized controlled trial. Issue 3 (March 2021) - Berger, Itai; Dakwar-Kawar, Ornella; Grossman, Ephraim S.; Nahum, Mor; Cohen Kadosh, Roi
Highlights: Transcranial random noise stimulation (tRNS) improved clinical symptoms in unmedicated children with ADHD. The improvement using tRNS was greater than transcranial direct current stimulation (tDCS) with a montage that was highlighted as promising in previous meta-analyses. The effect of intervention yielded further improvement after completion of treatment, suggesting a neuroplasticity-related effect. Abstract: Objective: Improving symptomology and cognitive deficits in neurodevelopmental disorders is a crucial challenge. We examined whether neurostimulation protocols, which have been shown to yield long-term effects when combined with cognitive training, could benefit children with Attention-deficit/hyperactivity-disorder (ADHD), the most common neurodevelopmental disorder in childhood. Methods: We used a randomized double-blind active-controlled crossover study of 19 unmedicated children with ADHD, who received either anodal transcranial direct current stimulation (tDCS) over the left dorsolateral prefrontal cortex (dlPFC) or random noise stimulation (tRNS) over the bilateral dlPFC, while completing executive functions training. Results: For our primary outcome, tRNS yielded a clinical improvement as indicated by the reduced ADHD rating-scale score from baseline, and in comparison to the changes observed in tDCS. The effect of brain stimulation one week after completion of treatment yielded further improvement, suggesting a neuroplasticity-related effect. Finally, tRNS improved working memory compared to tDCS, and a larger tRNS effect on ADHD rating-scale was predicted for those who showed the greatest improvement in working memory. Conclusions: We found that our intervention can have a lasting effect, rather than a merely immediate effect as was shown for in previous medical interventions in ADHD. Significance: Our results provide a promising direction toward a novel intervention in ADHD.